(untitled) (International Journal of Engineering and Computer Science, 2017)
Information Retrieval is mainly used for offering the fair information at the right time and also retrieving the necessary information in the desired form. Information systems which are strongly describes what the user need. The main intension of retrieval strategy states that the level of relevancy between the document and the query increases with increase in the number of items .The retrieval strategy are used for retrieving the information from highest ranked documents based on precision and recall. Different Retrieval Utilities are used to progress the performance of IR strategies. In this paper, specified the various retrieval strategies and utilities which are playing a major role in estimating the performance of IR.